PENGARUH TRANSAKSI HUBUNGAN ISTIMEWA, TRANSFER PRICING TERHADAP KEPATUHAN WAJIB PAJAK DENGAN PMK172/2023 SEBAGAI PEMODERASI - Liem Sien Niang; Regina Jansen Arsjah (JURNAL LENTERA BISNIS, 2025)
Development of the business world and improvement amount transaction must taxes affected​ Special relationship background p issuance of PMK 172 of 2023. The issuance of PMK 172 of 2023 aims to can give a sense of certainty law , justice and convenience implementation rights and obligations for the obligatory tax . Research This own objective For analyze a connection between transaction Special relationship , transfer pricing , compliance must tax and the implementation of PMK 172 of 2023 as moderation .​ Study​ This using report data finance Non- financial companies listed on the Indonesia Stock Exchange (IDX) for period 201 5 –20 24 . Determination​ sample use method purposive sampling with sample as many as 12 companies for 10 years consecutive so that sample amount to 120 and use application Eviews . Research results This show that transaction connection special influential negative to compliance must tax . Transfer pricing influential positive to compliance must tax . Implementation PMK 172 of 2023 strengthens influence transaction connection special and transfer pricing to compliance must tax as moderation